Events - Igor V. Karyakin; Elvira G. Nikolenko (Пернатые хищники и их охрана)
White-Tailed Sea Eagle Conference 2024 “Strengthening White-tailed Eagle network toward Southern Europe and Mediterranean countries” was held on September 15–21, 2024 in Osijek, Croatia.